2017
DOI: 10.5465/annals.2014.0078
|View full text |Cite
|
Sign up to set email alerts
|

The Process of Postmerger Integration: A Review and Agenda for Future Research

Abstract: Mergers and acquisitions continue to be prevalent despite frequently yielding disappointing outcomes. Post-merger integration plays a critical role in M&A success, yet many questions about M&A implementation remain unanswered. In this article, we review research on post-merger integration, which we organize around strategic integration, sociocultural integration, and experience and learning. We then lay out a research agenda that centers on expanding our understanding of processual dynamics in post-merger inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

14
423
1
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 295 publications
(441 citation statements)
references
References 192 publications
(205 reference statements)
14
423
1
3
Order By: Relevance
“…The PMI process typically comes up against obstacles related to capturing synergy, client disruption, structural integration, employee retention, loss of identity and/or independence, customer retention, emotional trauma, loss of status, and learning challenges. These are so diverse in nature and magnitude that they have given rise to multiple definitions of PMI (see discussion in Graebner et al 2016). Here, we define post-merger integration as the process that unfolds in the aftermath of the deal closure to reconfigure merging firms by redeploying, adding, or divesting resources, lines of products or entire businesses, in order to achieve the expected combination benefits.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The PMI process typically comes up against obstacles related to capturing synergy, client disruption, structural integration, employee retention, loss of identity and/or independence, customer retention, emotional trauma, loss of status, and learning challenges. These are so diverse in nature and magnitude that they have given rise to multiple definitions of PMI (see discussion in Graebner et al 2016). Here, we define post-merger integration as the process that unfolds in the aftermath of the deal closure to reconfigure merging firms by redeploying, adding, or divesting resources, lines of products or entire businesses, in order to achieve the expected combination benefits.…”
mentioning
confidence: 99%
“…Other work on PMI has emphasized learning and more sociocultural perspectives, going beyond the scope of this paper (for a comprehensive review of PMI studies, see Graebner et al 2016). …”
mentioning
confidence: 99%
“…Nevertheless, an interesting suggestion in the literature is to focus on emotions during socio-cultural integration. Whereas the literature largely focuses on the negative (e.g., Graebner et al, 2017), positivity has been found to be an important contributor to (e.g., Kusstatscher, 2006;Raitis et al, 2017), and therefore a fruitful topic of research on, socio-cultural integration.…”
Section: Propositions and Conclusionmentioning
confidence: 99%
“…Especially participative, reflective, and positive communication enhances socio-cultural integration (Clayton, 2010). Although previous studies have highlighted the importance of communication (e.g., Schweiger and DeNisi, 1991;Weber and Tarba, 2010;Angwin, 2016), the need for a deeper understanding of specific communication practices and tools used in socio-cultural integration persists (Graebner et al, 2017). The effectiveness of different communication means for dealing with conflict during socio-cultural integration, therefore, necessitates further research (Weber and Drori, 2011).…”
Section: Propositions and Conclusionmentioning
confidence: 99%
See 1 more Smart Citation